The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.1055/s-0038-1666912
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tsetse (Glossina morsitans morsitans Westw.) (Diptera: Glossinidae) Salivary Gland Homogenate on Coagulation and Fibrinolysis

Abstract: SummaryThe saliva of the tsetse, Glossina morsitans morsitans Westwood, has antithrombin anticoagulant activity and inhibits thrombin’s esterolytic activity. It has no other detectable anticoagulant properties. The anticoagulant elutes in a single peak on Sephadex fraction, is immediately acting, heat and storage stable, and has a molecular weight of 11-13,000. Unlike heparin it is not neutralized by protamine sulphate or toluidine blue and does not require the co-factor, antithrombin III, for optimal anticoag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…However, it was not until 1966 that Hawkins (8) determined that all of the anticoagulant activity present in salivary extracts of Glossina austeni could be attributed to the inhibition of thrombin, the terminal protease in the mammalian coagulation cascade. A similar antithrombin activity was later identified in G. morsitans (9), and in 1996 we reported the purification and characterization of this low molecular weight anticoagulant, which we named the tsetse thrombin inhibitor (TTI) (10). In addition to its small size (3,530 Da), TTI is one of the most potent (K i * ϭ 584 fM) naturally occurring anticoagulants ever identified, with remarkable specificity for thrombin.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, it was not until 1966 that Hawkins (8) determined that all of the anticoagulant activity present in salivary extracts of Glossina austeni could be attributed to the inhibition of thrombin, the terminal protease in the mammalian coagulation cascade. A similar antithrombin activity was later identified in G. morsitans (9), and in 1996 we reported the purification and characterization of this low molecular weight anticoagulant, which we named the tsetse thrombin inhibitor (TTI) (10). In addition to its small size (3,530 Da), TTI is one of the most potent (K i * ϭ 584 fM) naturally occurring anticoagulants ever identified, with remarkable specificity for thrombin.…”
Section: Discussionmentioning
confidence: 67%
“…These bloodfeeding insects have been known for decades to produce a potent salivary anticoagulant (6). First characterized as an ''antikinase'' (7), this activity was ultimately identified as an inhibitor of thrombin (8,9). Recently, the tsetse thrombin inhibitor (TTI), a potent (K i * ϭ 584 fM) 32-aa peptide, was purified to homogeneity from salivary gland extracts of Glossina morsitans morsitans (10).…”
Section: Introductionmentioning
confidence: 99%
“…Among the known tsetse saliva components are anti-hemostatic proteins [26], [27], [28], which include a potent anticoagulant thrombin inhibitor (TTI) [29], [30], and an anti-thrombotic apyrase (5′Nuclease) with dual inhibitory action that can bind to the fibrinogen receptor (GPIIb/IIIa) and inhibit ADP-induced platelet responses [31]. In addition, two abundant proteins (Tsal1 and Tsal2) have been described with DNA/RNA non-specific nucleic acid binding [26], [32], [33].…”
Section: Introductionmentioning
confidence: 99%
“…However, molecular information on the individual tsetse salivary proteins and their biological activity remains scanty. Previous studies on Glossina morsitans saliva have reported the presence of a 11.3 kDa inhibitor of thrombin serine protease and esterase activities (Parker and Mant, 1979) and a 430 kDa protein fraction that inhibited the ADP-induced thrombocyte aggregation (Mant and Parker, 1981). In addition, a potent 32 AA blood meal-induced tsetse thrombin inhibitor (TTI), was characterised in salivary gland extracts.…”
Section: Introductionmentioning
confidence: 99%